Synthesis, characterization, computational and dyeing behavior of Cu(II) and Zn(II) metal complexes derived from azo-Schiff bases containing phenol derivatives - Hemmat A. Elbadawy; Ali Eldissouky; Morsy Ahmed El-Apasery; Doaa S. Elsayed; Entesar. A. Alaswad (BMC Chemistry)
Abstract This study discusses the synthesis, characterization, and applications of two novel azo-Schiff bases, HL1 and HL2, derived from HL, 4-((3-formyl-4-hydroxyphenyl)diazenyl)benzenesulfonamide with o-aminophenol and o-amino-thiophenol, respectively, and their Cu(II) and Zn(II) complexes. Stability, dyeing, biological activity, and computational investigations with experimental data are examined. HL1, HL2 and their metal complexes were fully characterized utilizing different physicochemical techniques, such as UV-Vis, FTIR, mass spectra, thermal analysis (TGA, DTG and DTA), as well as EPR, molar conductivity measurements for metal complexes. The experimental findings showed that the metals were ligated to the azo-Schiff bases, HL1 and HL2 via the azomethine-N and phenolic-O or thiolato-S, respectively. The properties of the compounds as polyester fabric dyes were examined. They were evaluated for color fastness to washing, rubbing, and perspiration using ISO 105-C02:1989, X12:1987, and E04:1989. The colored materials’ superior intra-fiber diffusion inside the substrate may explain their exceptional washing and rubbing and perspiration fastness. In vitro antimicrobial efficiency of all products was explored against a panel of pathogenic bacteria, including Gram-positive bacteria Staphylococcus aureus and Bacillus subtilis, Gram-negative bacteria Escherichia coli and Proteus vulgaris, and pathogenic fungi Aspergillus flavus and Candida albicans, compared to Gentamycin and Ketoconazole as standards. Additionally, the cytotoxicity of developed compounds in one human cell line, lung carcinoma (A-549), was examined, demonstrating how chelation and molecular structure can affect anticancer activity. Compared to Ascorbic acid, their antioxidant activities were evaluated, and their ability to reduce DPPH radical was affected by molecular composition and structure. For free ligands, HL1 > HL > HL2 decreased power. For metal complexes, [Cu(L1)₂]0.5 H₂O was more potent than [Zn(L1)₂].2H₂O, but [Zn(L2)₂].2H₂O >[Cu(L2)₂]0.3 H₂O, as antioxidant. The applied computational studies and molecular docking on the proposed structures of the complexes were in good agreement with the experimental results.